(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Poly[ethylenediaminetetraacetato-aqua-disodium-nickel(II)] was investigated by Fourier Transform Infrared (FT-IR) spectroscopy to elucidate its coordination behavior and structural features. The FT-IR spectrum revealed characteristic absorption bands associated with coordinated water molecules, carboxylate groups, mine functionalities, and metal-ligand bonds. Broad bands at 3461 and 3374 cm-1 confirmed the presence of coordinated water molecules, while bands at 1591 and 1475 cm-1 corresponded to asymmetric stretching vibrations of coordinated carboxylate groups. The symmetric stretching vibrations appeared at 1393 and 1359 cm-1, indicating the involvement of carboxylate oxygen atoms in metal coordination. Bands observed at 1316 and 1295 cm-1 were assigned to C-N stretching vibrations of coordinated amine groups. The low-frequency absorptions between 709 and 444 cm-1 were attributed to Ni-O and Ni-N bonds, confirming the formation of a stable nickel(II)-EDTA coordination network. The obtained results support the proposed octahedral coordination environment around the Ni(II) center and demonstrate the successful synthesis of the coordination polymer.